Designing Branding Kampoeng Bebek and Telur Asin Sidoarjo Kebonsari Village Based Education Tourism In An Effort To Increase Tourism Potential Tourism Village - Estherlita, Tria Kuswidya; Bahruddin, Muh; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2016)
The purpose of designing branding Kampoeng Bebek is to increase the potential of the village as an educational tourist attraction in Sidoarjo. This research was conducted with qualitative methods obtained through the interview process, documentation, observation and study literature so that the data used is capable of supporting the creation of a design concept branding Kampoeng duck. The concept in this study were obtained from the SWOT analysis, STP, and the USP cornered back so find the keyword "fresh" will be used in this study. In the dictionary of KBBI "fresh" has a new meaning or concept then refurbish the deed who wants to show up is the process of update that is manifested by the presence of education and renewal in the process of the introduction of the educational tours in Kampoeng Bebek. So this will be visualized in design creative with objects that characterizes mojosari duck icon is processed and in Kampoeng Bebek and Telur Asin. The result of designing branding is to create Kampoeng bebek known to travelers with the means of education. Keywords: Branding, Kampoeng Bebek and Telur Asin, Village Kebonsari Sidoarjo, Education Tourism.